Host defense triggers rapid adaptive radiation in experimentally evolving parasites. Issue 2 (1st April 2019) - Bush, Sarah E.; Villa, Scott M.; Altuna, Juan C.; Johnson, Kevin P.; Shapiro, Michael D.; Clayton, Dale H.
Abstract: Adaptive radiation occurs when the members of a single lineage evolve different adaptive forms in response to selection imposed by competitors or predators. Iconic examples include Darwin's finches, Caribbean anoles, and Hawaiian silverswords, all of which live on islands. Although adaptive radiation is thought to be an important generator of biodiversity, most studies concern groups that have already diversified. Here, we take the opposite approach. We experimentally triggered diversification in the descendants of a single population of host-specific parasites confined to different host "islands." We show rapid adaptive divergence of experimentally evolving feather lice in response to preening, which is a bird's main defense against ectoparasites. We demonstrate that host defense exerts strong phenotypic selection for crypsis in lice transferred to different colored rock pigeons ( Columba livia ). During four years of experimental evolution (∼60 generations), the lice evolved heritable differences in color. Strikingly, the observed color differences spanned the range of phenotypes found among congeneric lice adapted to other species of birds. To our knowledge, this is the first real-time demonstration that microevolution is fast enough to simulate millions of years of macroevolutionary change. Our results further indicate that host-mediated selection triggers rapid divergence in the adaptive radiation of parasites, which are among the most diverse organisms on Earth.